Sistem Akuaponik Dapat Meningkatkan Pertumbuhan dan Tingkat Kelangsungan Hidup Ikan Mas (Cyprinus carpio) (AQUAPONIC SYSTEMS COULD INCREASE THE GROWTH AND SURVIVAL OF COMMON CARP (CYPRINUS CARPIO)) - Asni, Asni; Rahim, Rahim; Marwayanti, Marwayanti (Jurnal Veteriner, 2020)
Carp (Cyprinus carpio) is one of the superior freshwater aquaculture products in the fisheries subsector. However, until now the production of carp cultivation is still carried out in a conventional manner which allows a high mortality rate of the fish. One way to overcome the high death rate of the fish are by maintaining an aquaponics system. This study aims to determine the effect of aquaponic and conventional system on the growth and survival rates of carp. This study used a completely randomized design consisting of two treatments and three replications. Treatment A (aquaponic system) and Treatment B (conventional system). Analysis of the data used is the t-test. The test fish used in this study were 168 carp seeds measuring 10 cm long in size. Parameters observed were biological parameters, including; absolute growth, specific growth rate, survival, and feed conversion ratio, while water quality parameters include ammonium, nitrite, nitrate, pH, dissolved oxygen. The results of the study on both treatments showed that the average absolute growth of treatment was (6.20 g) and treatment B (5.73 g), specific growth in treatment A (3.31 g) and treatment B (2.24 g). ), feed conversion ratio of treatment A (4.24) and treatment B (5.58), the survival of treatment A (64.28%) and treatment B (52.38%). Statistical analysis of t-test on both treatments showed that the performance of aquaponic systems and conventional systems had a significant effect on absolute growth, specific growth rates, the survival of carp, and water quality. So it can be concluded that carp cultivation with the aquaponic system shows a better rate of growth and survival and water quality compared to the conventional system.